Alternative in strengthening bureaucratic neutrality through political culture in the 2019 election in Boalemo Regency - Ramli Mahmud Ramli Mahmud (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2022)
This article aims to examine and analyze the issue of bureaucratic neutrality in the perspective of political culture in the 2019 elections in Boalemo County. The problem of bureaucratic impartiality in elections is caused by the political culture of kaula. To answer the problem in question, this study uses a qualitative method with a phenomenological approach where the researcher is a key informant in data collection through interviews and documentation, especially literature related to the same object. The results showed that ASNs in the structural and functional ranks of teachers tend not to be neutral due to the Regent as the regional head, political attitudes and choices tend to kaula political culture. Meanwhile, the bureaucracy in the functional ranks of Health tends to be neutral and prioritizes the value of rationality based on the political culture of the participants. Based on these findings, it is necessary to strengthen the political culture of participants for the bureaucracy in the regions through socialization and political education. Keywords: Political Culture, Bureaucracy, Elections 2019